Peningkatan Kemampuan Motorik Halus Anak melalui Permainan Menjepit Pom Pom Berwarna di Play Group - Maidona, Siska; Saridewi, Saridewi (Penerbit Aksara Rentaka Siar (ARS), 2019)
The purpose of this study is to improve the Fine Motoric Ability of Children through the Game of Pinning Color Pom in the Citra Al Madina Padang Play Group. So that children can improve children's fine motor skills by clamping colored poms. This type of research is class action research with quantitative methods. Based on data analysis, the results of research on children's understanding increased, as seen from children playing colored poms in the first cycle pouring pom poms with a container of only 8.3%, it turns out that in cycle II it increased to 50% means pom pom colored has increased.